Substrate-inducible and antibiotic-free high-level 4-hydroxyvaleric acid production in engineered Escherichia coli - Sathesh-Prabu, Chandran; Tiwari, Rameshwar; Lee, Sung Kuk (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, we developed a levulinic acid (LA)-inducible and antibiotic-free plasmid system mediated by HpdR/PhpdH and infA-complementation to produce 4-hydroxyvaleric acid (4-HV) from LA in an engineered Escherichia coli strain. The system was efficiently induced by the addition of the substrate, LA, and resulted in dose-dependent tight control and fine-tuning of gene expression. By engineering the 5′ untranslated region (UTR) of hpdR mRNA, the gene expression level of green fluorescent protein (GFP) increased by at least 2-fold under the hpdH promoter. Further, by evaluating the robustness and plasmid stability of the proposed system, the engineered strain, IRV750f, expressing the engineered 3-hydroxybutyrate dehydrogenase (3HBDH*) and formate dehydrogenase (CbFDH), produced 82 g/L of 4-HV from LA, with a productivity of 3.4 g/L/h and molar conversion of 92% in the fed-batch cultivation (5 L fermenter) without the addition of antibiotics and external inducers. Overall, the reported system was identified to be highly beneficial for large-scale and cost-effective microbial production of value-added products and bulk chemicals from the renewable substrate, LA.